Comparative Analysis of Existing Blockchain Based Certification DApps - Avnish Singh Jat (International Journal of Advanced Science and Technology, 2020)
This research paper focuses on comparison of existing solution for the verification of the authenticity of issued professional certificates by organisation through blockchain. We have selected few projects in which the issued certificates are registered on the blockchain so that any third party who would need to verify the authenticity of a certificate can do so. The purpose of this paper is to compare the ongoing implementation of blockchain based certification in all technical aspects, find the existing loopholes and suggests the possible amendments.